La iconografía de los queros del Museo de La Plata: Primeras aproximaciones interpretativas - Paez, Maria Cecilia (2019)
The wooden vases of the Andean Colonial Period stand out for their symbolism and polychromy, gathering iconographic elements typical of the American pre-Hispanic idiosyncrasy in a design structure that finds similarities with the European Baroque. This network of signs reflects the complex reality of the Inca elites, with whom the use of keros is linked, in the new political and social context imposed by the Colonial order. In this work we present the analysis of 10 wooden vases coming from Cusco, deposited in the Museum of La Plata (Argentina). We propose that its iconography constitute an alternative form to the orality for the reproduction of the collective memory and the strengthening of the indigenous identities.